Marketing Mix Practices Among Women Culinary Entrepreneurs In Indonesia - Ani Rakhmanita; Desy Tri Anggarini; Arief Fahruri (Asosiasi Dosen Muda Indonesia, 2025)
This study attempts to investigate how the marketing mix is practiced among women culinary entrepreneurs. A descriptive approach was used, with data collected through closed-ended questionnaires from 75 women culinary entrepreneurs. The results show that women culinary entrepreneurs in Bogor City do not implement several elements of the marketing mix, and their source of knowledge about the marketing mix is derived solely from business experience. The limited use of marketing mix elements is attributed to constraints faced by women culinary entrepreneurs, particularly limited working capital. A limitation of this study is its static nature, as it provides a descriptive overview of marketing mix practices without in-depth insight into the effects of these practices. Future research is suggested to empirically investigate the influence of marketing mix practices among women culinary entrepreneurs using a mixed-method approach.